Financial market disturbances as sources of business cycle fluctuations in Finland - Hanna Freystätter (Bank of Finland, 2010)
This paper studies financial market disturbances as sources of investment fluctuations in Finland during 1995 2008. We construct a DSGE model of the Finnish economy that incorporates two domestic financial market shocks and financial frictions in the form of a BGG financial accelerator. We investigate empirically the importance of financial market frictions and disturbances by estimating the model using a Bayesian Maximum Likelihood approach. The empirical evidence points to an operative financial accelerator mechanism in Finland. Our key result is that disturbances originating in the financial sector have played a significant role in the historical variation of investment activities in Finland. Even allowing for several shocks stemming from both domestic sources and the international economy, domestic financial market shocks emerge as key drivers of recent business cycle fluctuations in Finland
URN:NBN:fi:bof-20140807306
Keywords: 330